A simple sleeve test worn during exercise to quantify skin feel and willingness to pay for wool fabric samples. Issue 11 (July 2015) - Doyle, Emma K; Tester, David; Thompson, John
This paper describes a protocol in which female participants scored a range of sensory attributes and applied a financial value to sleeves made from knitted fabric after undertaking a 30 minute circuit training program in a gym. Each participant wore a test and a control sleeve which they scored a line scale for breathability (anchored by the words 'doesn't breathe well'/'breathes well'), skin feel (anchored by the words 'prickly itchy'/'soft smooth'), feel after exercise (anchored by the words 'damp sweaty'/'dry') and overall comfort (anchored by the words 'very uncomfortable'/'very comfortable'). Participants also estimated their willingness to pay (WTP) for two long-sleeved next-to-skin garments made from the test and the control fabrics. All sensory scores and WTP estimates were positively correlated. Participant and sleeve fit impacted on sensory scores and WTP estimates. However, the significance of participant and fit effects were reduced if differences between the test and control sleeves were analysed and therefore this difference was a better measure of the fabric attributes than simply meaning the test fabric score. The sleeve protocol provided a relatively inexpensive and simple means to score fabrics on sensory attributes and WTP.